Optimism and Wishful Thinking: Consistency Across Populations in Children's Expectations for the Future. Issue 4 (16th August 2019) - Bamford, Christi; Lagattuta, Kristin Hansen
Abstract : Two studies investigated 5‐ to 10‐year‐olds' ( N  = 194) positivity bias when forecasting the future. Children from two geographic locations (mostly Caucasian, higher income college town; mostly African American, lower income urban community) completed a future expectations task (FET). For multiple scenarios, children predicted whether a positive versus negative (optimism items) or a positive versus extraordinary positive (wishful thinking items) outcome would occur, including its likelihood. In both samples, optimism and wishful thinking decreased with age, optimism was higher than wishful thinking, children did not show a comparative self‐optimism bias, and individual differences in the FET optimism score correlated with self‐reported dispositional optimism and hope. Exploratory comparisons revealed between‐sample equivalence in responses to all measures, except for less tempered wishful thinking in the urban community.